ATRT-SHH comprises three molecular subgroups with characteristic clinical and histopathological features and prognostic significance - Federico, Aniello; Thomas, Christian; Miskiewicz, Katarzyna; Woltering, Niklas; Zin, Francesca; Nemes, Karolina; Bison, Brigitte; Johann, Pascal D; Hawes, Debra; Bens, Susanne; Kordes, Uwe; Albrecht, Steffen; et al. (Acta neuropathologica, 2022)
Atypical teratoid/rhabdoid tumor (ATRT) is an aggressive central nervous system tumor characterized by loss of SMARCB1/INI1 protein expression and comprises three distinct molecular groups, ATRT-TYR, ATRT-MYC and ATRT-SHH. ATRT-SHH represents the largest molecular group and is heterogeneous with regard to age, tumor location and epigenetic profile. We, therefore, aimed to investigate if heterogeneity within ATRT-SHH might also have biological and clinical importance. Consensus clustering of DNA methylation profiles and confirmatory t-SNE analysis of 65 ATRT-SHH yielded three robust molecular subgroups, i.e., SHH-1A, SHH-1B and SHH-2. These subgroups differed by median age of onset (SHH-1A: 18 months, SHH-1B: 107 months, SHH-2: 13 months) and tumor location (SHH-1A: 88% supratentorial; SHH-1B: 85% supratentorial; SHH-2: 93% infratentorial, often extending to the pineal region). Subgroups showed comparable SMARCB1 mutational profiles, but pathogenic/likely pathogenic SMARCB1 germline variants were over-represented in SHH-2 (63%) as compared to SHH-1A (20%) and SHH-1B (0%). Protein expression of proneural marker ASCL1 (enriched in SHH-1B) and glial markers OLIG2 and GFAP (absent in SHH-2) as well as global mRNA expression patterns differed, but all subgroups were characterized by overexpression of SHH as well as Notch pathway members. In a Drosophila model, knockdown of Snr1 (the fly homologue of SMARCB1) in hedgehog activated cells not only altered hedgehog signaling, but also caused aberrant Notch signaling and formation of tumor-like structures. Finally, on survival analysis, molecular subgroup and age of onset (but not ASCL1 staining status) were independently associated with overall survival, older patients (> 3 years) harboring SHH-1B experiencing relatively favorable outcome. In conclusion, ATRT-SHH comprises three subgroups characterized by SHH and Notch pathway activation, but divergent molecular and clinical features. Our data suggest that molecular subgrouping of ATRT-SHH has prognostic relevance and might aid to stratify patients within future clinical trials.
Keywords: ASCL1; proteiny hedgehog; Humans; Atypical teratoid/rhabdoid tumor; Gene expression; Neuroradiology; lidé; neuroepitelové nádory; gen SMARCB1; DNA methylation profiling; GFAP; Overall survival; nádory centrálního nervového systému; Hedgehog Proteins; SMARCB1 Protein; DNA Methylation; Central Nervous System Neoplasms; metylace DNA; Teratoma; OLIG2; prognóza; Neoplasms, Neuroepithelial; Sonic hedgehog; rhabdoidní nádor; Rhabdoid Tumor; teratom; Prognosis